Lugra Saree of the East Indian Community - Mumbai Archive Project Team (Jio Institute, 2024)
Through modern adaptations and preservation efforts, the Lugra saree has reemerged in the East Indian community as a symbol of their native heritage. Though East Indian men do not adhere to a particular dress code, they wear shirts in matching colours with personalized embellishments reflecting their interests and tastes.